a Comparison of Lipid Profile in Ischemic Stroke Patiens with Diabetes Mellitus and Non-Diabetes Mellitus at Rumah Sakit Umum Daerah Ciamis 2020 - Niken Puspa Kuspriyanti; Dina Nabila Lestari; Sofie Kaniawati (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Diabetes mellitus causes lipid profile abnormalities, resulting in dyslipidemia in diabetic patients leading to ischemic stroke. This research aims to contrast lipid profiles in ischemic stroke patients with type 2 diabetes mellitus (T2DM) and non-type 2 diabetes mellitus (non-T2DM) to prevent stroke recurrence, treat dyslipidemia in diabetes mellitus, and evaluate for treatment of T2DM and non-T2DM ischemic stroke patients. A cross-sectional design was conducted at RSUD Ciamis using secondary medical record data in 2020. The data was collected using a nonprobability sampling approach, with the sampling extent determined by inclusion and exclusion criteria. Univariate analysis was used to determine the quantity and calculation. Besides, an independent t-test and chi-square test was utilized to test two hypotheses in bivariate analysis. Multifaceted analysis in age, gender, hypertension, and coronary heart disease was incorporated to observe its influence on T2DM and non-T2DM ischemic stroke patients. By using four lipid profile indicators, the differences were only in the triglyceride. While the total cholesterol, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) were insignificant. Meanwhile, hypertension and coronary heart disease (CHD) significantly affect the incidence of ischemic stroke.